Improved N‐acetylneuraminic acid bioproduction by optimizing pathway for reducing intermediate accumulation. Issue 3 (14th November 2022) - Guo, Haoyu; Tian, Rongzhen; Wang, Chenyun; Zhao, Runzhi; Lv, Xueqin; Liu, Long; Liu, Yanfeng
Abstract: N ‐acetylneuraminic acid (NeuAc), which has been widely used as a nutraceutical and pharmaceutical intermediate, plays an important role in improving brain development and cognition while enhancing immunity. Bacillus subtilis, generally regarded as a food‐safe microorganism, is suitable for developing as a chassis cell for efficient NeuAc synthesis. However, accumulated intermediates can lead to metabolic bottlenecks for NeuAc synthesis. To eliminate the accumulated byproduct N ‐acetylglucosamine (GlcNAc), the UDP‐GlcNAc epimerase pathway without GlcNAc production was first reconstructed and optimized in B. subtilis, resulting in the NeuAc titer increase of 5.9 g/L with GlcNAc elimination. In addition, to reduce another accumulated byproduct N ‐acetylmannosamine (ManNAc), the directed evolution of N ‐acetylneuraminic acid synthase and the enhancement of phosphoenolpyruvate supply was implemented. Using this strategy, ManNAc decreased by 46.3%, and the NeuAc titer increased by 54.9%, reaching 7.9 g/L. Finally, the maximum titer of NeuAc in a 3‐L fermenter reached 21.8 g/L with a productivity of 0.34 g/L/h. Abstract : 1. To eliminate the extensively accumulated by‐product N ‐acetylglucosamine (GlcNAc), the UDP‐GlcNAc epimerase (NeuC) pathway without GlcNAc production was firstly reconstructed and optimized in Bacillus subtilis, and thereby NeuAc titer increased to 5.9 g/L and the by‐product GlcNAc was eliminated. 2. The maximum titer of NeuAc in fed‐batch fermentation in a 3‐L fermenter was 21.8 g/L.